Government Policy for the Stable Growth of the Sharing Economy - Min Jung Kim (Korea Development Institute (KDI), 2017)
The sharing economy is expected to contribute to the enhancement of social welfare with its wide range of benefits, including creation of new transactions and promotional and market testing opportunities, if risk factors such as crowding out of existing transactions and transaction and social risks can be properly controlled. Accordingly, an institutional framework is needed to support the stable growth of the sharing economy and the unique characteristics of non-professional, peer-to-peer transactions should be reflected in tandem with regulatory equity between existing and sharing economy suppliers. For this, transaction volume-based regulations are recommended. Furthermore, to secure regulatory effectiveness and to alleviate transaction risks, the pertinent obligations must be imposed on sharing platforms. - There is increasing demand for in-depth analysis of and policy response to the sharing economy which is growing fast on the back of technological advances. - Within the concept of the sharing economy, idle assets have great significance. The sharing economy basically involves transactions between nonprofessional peers. - Primary benefits expected from the sharing economy are creation of new transactions and resulting improvements in the welfare of sharing economy participants. - Businesses participating in the sharing economy can also expect promotional and market testing effects. - Other expected benefits include vitalization of local economy and reduction in environmental costs. - The sharing economy could crowd out some existing transactions that provide similar services. - The crowding out of existing transactions will exacerbate when regulations are applied unfairly to suppliers from existing and sharing businesses. - The sharing economy encompasses several transaction risks including information asymmetry, uncertainty in ex-post handling and weak trust in platforms. - Negative external effects could be triggered, marring social safety. - In laying the institutional framework to support the stable growth of the sharing economy, the government must consider both the economy's unique characteristics and regulatory equity. - Transaction volume-based regulations are recommended for the sharing economy. - To strengthen the effectiveness of transaction volume-based regulations, certain obligations must be imposed on platforms. - As for transaction risks, government policies need to play a supplementary role while placing its focus on sharing platforms.
Keywords: 330